2011
DOI: 10.4093/dmj.2011.35.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Chemerin Levels and Cardiometabolic Parameters and Degree of Coronary Stenosis in Korean Patients with Coronary Artery Disease

Abstract: BackgroundChemerin is a novel adipokine that is associated with inflammation and adipogenesis. However, it remains unclear whether chemerin is involved in patients with cardiovascular disease. We investigated whether the serum chemerin levels of Korean patients with coronary artery disease correlated with specific cardiometabolic parameters.MethodsIn total, 131 patients, all of whom had coronary artery stenosis exceeding 50%, participated in this study. Their serum chemerin levels and cardiometabolic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 28 publications
3
33
0
1
Order By: Relevance
“…In this study, positive correlations were reported between serum chemerin levels and fasting glucose, triglycerides, total cholesterol, and High-sensitivity C-reactive protein (HsCRP) [Hah et al 2011]. A correlation between circulating chemerin levels and CAD severity were found in recent case-control studies.…”
Section: Chemerin and Cardiovascular Diseasesmentioning
confidence: 59%
See 1 more Smart Citation
“…In this study, positive correlations were reported between serum chemerin levels and fasting glucose, triglycerides, total cholesterol, and High-sensitivity C-reactive protein (HsCRP) [Hah et al 2011]. A correlation between circulating chemerin levels and CAD severity were found in recent case-control studies.…”
Section: Chemerin and Cardiovascular Diseasesmentioning
confidence: 59%
“…Also, Dong and colleagues have found higher levels of chemerin in MetS patients with CAD in comparison with MetS patients without CAD [Dong et al 2011] (Table 2). Although significantly high serum chemerin levels were found in CAD, it is not clearly known if this increased level represents a predictor for CAD or is a result of atherosclerotic plaque morphology [Lehrke et al 2009;Hah et al 2011]. …”
Section: Chemerin and Cardiovascular Diseasesmentioning
confidence: 99%
“…Chemerin has indeed been proposed as a predictive marker of cardiovascular risk [27,28], and previous works have demonstrated that circulating chemerin concentrations correlate with several cardiometabolic parameters and with the severity of coronary artery disease [29][30][31]. Moreover, chemerin and CMKLR1 genes are both expressed by cells of the cardiovascular system, in which their levels have been shown to be positively correlated with the severity of cardiac pathologies such as atherosclerosis [32].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…In recent times, the adipose tissue is increasingly being recognized as an active endocrine organ [6,7]. This is so, as many molecules such as vaspin, omentin, adiponectin and a host of other Ekpe E. E. and Ekpe V. E.: Chemical Pathology of Chemerin and Its Link to Obesity and Type 2 Diabetes Mellitus: A Review molecules are derived from the adipocytes [8,9].…”
Section: Clinical Corrrelation Of Chemerin and Obesity And Diabates Mmentioning
confidence: 99%